PERSEPSI TOKOH MASYARAKAT KOTA TANJUNG PURA TENTANG ISU RIBA DALAM MENINGKATKAN MINAT MASYARAKAT MENABUNG DI BANK SYARIAH INDONESIA KCP STABAT - Fariz Arkhan; Diyan Yusri; Anjur Perkasa Alam (Program Studi Ekonomi Syariah Sekolah Tinggi Agama Islam Negeri Mandailing Natal, 2022)
Sharia Bank is a financial institution tasked with collecting funds and distributing funds as well as providing other services based on the principles of partnership, fairness, transparency and universality as well as conducting banking business activities based on sharia principles. The development of Islamic banks is currently quite fast, but lately Islamic bank customers have different perceptions of Islamic banking, where some people hear about news or issues circulating about the perception of public figures who say that Islamic banks still use the principle of usury. which is a benchmark for some people and raises its own doubts about saving in Islamic banks, this is caused by several factors. First, the lack of socialization carried out by Islamic banks. Second, the lack of understanding of public figures regarding the system and objectives of Islamic banking itself. The formulation of the problem in this research is how is the perception of community leaders in increasing people's interest in saving? This type of research is a field research (field research), and is descriptive qualitative. The results of this study state that the perception of public figures in increasing public interest in saving in Islamic banks is in the Good category. Good category, customers already understand what Islamic banking is like, customers already know Islamic banks and not a few customers who already understand Islamic banking, and the public confirms that there are issues circulating in the community where public figures still have the assumption that Islamic banks are no different from conventional banks, while the issue of usury on people's interest in saving Islamic banks is in the medium category, meaning that the issue of usury circulating among the public has quite an impact on people's perceptions, therapy does not have much impact on people's interest in saving.